The Effect of Schema Therapy on Aggressive Behaviour among Senior Secondary School Students in Oyo State, Nigeria - Augustina Ekeh; Titilayo Monsurat Musa; Adejare adelodun Adejumobi; Adeleye Adewale Olugbemiga (International Journal of Counseling and Psychotherapy, 2026)
Background: Pervasive aggressive behavior in secondary schools severely undermines school safety, yet conventional school guidance rarely addresses the underlying early maladaptive schemas. Objective: This study aims to investigate the effect of Schema Therapy on aggressive behavior among senior secondary school students in Oyo State, Nigeria. Methods: A quasi-experimental pretest-posttest control group design was employed, involving 116 Senior Secondary School II students with high aggression scores recruited via multistage sampling. The experimental group received a ten-week structured Schema Therapy protocol, while the control group received conventional counseling. Data were collected using the Aggressive Behaviour Questionnaire (α = 0.89) and analyzed using Analysis of Covariance (ANCOVA) at the .05 level. Results: Schema Therapy produced a statistically significant main effect in reducing student aggression compared to conventional counseling. Gender also had a significant main effect, with female students recording higher post-test aggression scores than males. No significant treatment-by-gender interaction occurred, demonstrating consistent therapeutic gains across participants. Conclusion: Schema Therapy is empirically superior to conventional guidance in reducing adolescent aggression regardless of gender. Originality/Value: This study brings scientific novelty to the field of counseling and psychotherapy by uncovering the efficacy of Schema Therapy in restructuring early maladaptive schemas within a non-Western educational context that has remained underexplored. These findings enrich empirical evidence while providing a strategic reference for school counselors and policymakers in developing sustainable interventions.